Revision of the South American wasp genus Alophophion Cushman, 1947 (Hymenoptera: Ichneumonidae: Ophioninae) - Erratum - Alvarado, Mabel (2014)
In: Alvarado M. 2014. Revision of the South American wasp genus Alophophion Cushman, 1947 (Hymenoptera: Ichneumonidae: Ophioninae). Revista peruana de biología 21(1): 003 - 060 (Mayo 2014), doi: http://doi.org/10.15381/rpb.v21i1.8245The following information on depository of the type material was not provided: Holotype of Alophophion atahualpai is housed in the Museo de Historia Natural, Universidad Nacional Mayor de San Marcos, Peru (MUSM); and, the holotype of A. carcanchoi, A. coquimboensis and A. yestay are housed in the American Entomological Institute, USA (AEIC).I thank Gavin Broad for bringing this problem to my attention.